ANALYSIS OF THE LEVEL OF NICOTINE DEPENDENCE AMONG TEENAGE SMOKERS IN SERANG CITY BANTEN PROVINCE - Jajang Ganjar Waluya; Lisnawati Yupartini; Soleh; Belvana Ainul Fitriyani (Nursing Sciences Journal, 2025)
Smoking is a serious public health problem with a high prevalence among adolescents, including in Serang City, where it reaches 18.17% among adolescents aged 15–24. The purpose of this study was to analyze the level of nicotine dependence among adolescent smokers and the factors influencing it in Serang City, Banten Province. This quantitative study used a cross-sectional study design to analyze the level of nicotine dependence and its influencing factors. The population was estimated at 3,698 active adolescent smokers in Serang City. The sample size was calculated using the Krejcie and Morgan method. The sample size was 351 individuals. The sampling technique used was consecutive sampling. The research instrument was the Fagerström Test for Nicotine Dependence (FTND). Analysis used the Chi-Square statistical test with a significance level of α = 5%. The results showed a significant relationship between age at smoking initiation, duration of smoking, and number of cigarettes consumed per day with the level of nicotine dependence. Early intervention through education, smoking cessation counseling, and restricting cigarette access for adolescents is essential to prevent long-term addiction.   Keywords: Nicotine Dependence, Adolescents, Cigarettes